Beliefs in the Future as a Positive Youth Development Construct: A Conceptual Review - Rachel C. F. Sun; Daniel T. L. Shek (The Scientific World Journal)
Beliefs in the future are an internalization of hope and optimism about future outcomes. This paper reviews and compares several theories of hope and optimism and highlights the features constituting beliefs in the future. This paper points out that beliefs in the future include a series of goal-directed thoughts and motivation, such as setting up valued and attainable goals, planning pathways, and maintaining self-confidence and mastery, so as to keep adolescents engaged in the pursuit of goals. This kind of personal mastery, together with sociocultural values, family, school, and peers are the antecedents leading to beliefs in the future, which is related to adolescents’ well-being and positive development. In order to cultivate adolescents’ beliefs in the future, enabling their ability to manipulate goal-directed thoughts and motivation and providing a supportive environment including their family, school, peers, and the society are recommended.